Hadits Tentang Pendidikan Akhlak dan Pendidikan Sosial - Astuti, Nita Yuli; Sujati, Budi (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
In Islam, moral education is education that comes from religious teachings and community culture by creating tranquility, tranquility, and peace in life. In Islamic teachings, we know the term hablumminannas, where we can see well with humans. This is one of the goals of moral education, where humans can relate and do good with others. Because we are supposed to be social beings who will always need other people. In a hadith clearly shows that the Prophet SAW was very fond of people who are noble and people who talk the most. In addition, another hadith also explains that we are commanded to love others, even as we love ourselves. The implementation of this love is to help each other and provide benefits to others. The love that is given to this fellow with the differences that exist, so that it doesn't happen. Keywords: Hadits, Education, Morals, Social